Spirit Harmoni Kosmos Dalam Ritual “Nyakak Bumi” Studi Living Islam di Ambunten Tengah, Sumenep - Chair, Badrul Munir (UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to clarify the spirit of cosmos harmony of Nyakak Bumi ritual in Ambunten coastal, Sumenep: Nyakak Bumi is a ritual that helded by Maduran society to be blessed and given fertility in their inveronment. The data collection is done by observation to the invironment and interview with informants in Ambunten, Sumenep-Madura. The obtained data is classified and analyzed using the analysis of cosmological approach, in which the symbols of Nyakak Bumi ritual to see the spirit of harmony that exists. Based on this research, it was found that Nyakak Bumi ritual have spirit of cosmos harmony in three forms, that is harmony between human beings, harmony between humans and the universe, and harmony between fellow elements of cosmos.